2019
DOI: 10.3390/ijerph16050824
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perceived Travel Time to and Reported Use of Food Retailers in Association with School Children’s Dietary Patterns

Abstract: Considering the association between the neighborhood food environment and individual eating behaviors, this study aimed to assess the association between parents’ reported use of food facilities by their children, and parental perceived travel time to food facilities, with their children’s dietary patterns. Parents reported the use of supermarkets, full-service and fast-food restaurants, and perceived travel time to these food retailers. To assess school children’s food consumption, a previous day dietary reca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“… 65 Indeed, in a previous study with children living in Florianópolis, the use of restaurants was associated with a higher consumption of foods composing a “Fast Food” pattern. 66 In addition, a study using data from the Brazilian Household Budget Survey (POF 2008-2009; n = 34 003 children up to 10 years old) found that a “ultra-processed food” pattern, characterized by foods such soft drinks, fast food, pizza, and sweets, was a very common choice among children when eating out. Since out-of-home meals are becoming increasingly popular in Brazil, 67 such findings demonstrate the need for policies aiming to limit the amount of ultra-processed foods offered in restaurants, especially those near schools.…”
Section: Discussionmentioning
confidence: 99%
“… 65 Indeed, in a previous study with children living in Florianópolis, the use of restaurants was associated with a higher consumption of foods composing a “Fast Food” pattern. 66 In addition, a study using data from the Brazilian Household Budget Survey (POF 2008-2009; n = 34 003 children up to 10 years old) found that a “ultra-processed food” pattern, characterized by foods such soft drinks, fast food, pizza, and sweets, was a very common choice among children when eating out. Since out-of-home meals are becoming increasingly popular in Brazil, 67 such findings demonstrate the need for policies aiming to limit the amount of ultra-processed foods offered in restaurants, especially those near schools.…”
Section: Discussionmentioning
confidence: 99%
“…This is a cross-sectional study nested within a broader investigation which general objective was to review the trend in the prevalence of overweight/obesity and associated factors in schoolchildren, aged 7 to 14 years, based on the comparison of data obtained at three investigation time-points: 2002, 2007 and 2012/2013 [13][14][15][24][25][26][27] . In this article, BI and anthropometric data were reviewed, as well as behavior of students in relation to purgative trends for weight control and binge eating, collected in the third wave (2012/2013) 13,15,[24][25][26][27] .…”
Section: Methodsmentioning
confidence: 99%
“…In each stratum, the schools included in the study were randomly selected, by simple drawing. Subsequently, the selection of classes to be evaluated in each school was carried out, through a systematic sampling process, based on the list of students available in each school 13,15,[24][25][26][27] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two papers in this issue explore this idea further by investigating how perceptions of proximity influence food-related decision making and the factors that might influence these perceptions. Alves and colleagues [7] investigated parent’s perception of travel time to supermarkets and restaurants and reported that greater perceived travel time to restaurants (fast-food or full-service), but not supermarkets, was associated with a children’s dietary pattern consistent with less fast-food consumption and this effect was consistent across income levels. The concept of perceived distance was also investigated by Baldock and colleagues [8], who reported on the discrepancy between the perceived and objective distance to local fruit and vegetable retailers and the factors associated with these differences.…”
Section: The Importance Of Perceptionsmentioning
confidence: 99%